Formulation and evaluation of transdermal patch of Etodolac - Sammal, Nidhi; Dutta, Disha; Kandpal, Ankur (Journal of Neonatal Surgery, 2025)
A transdermal patch is an adhesive medication that goes through your skin and into the bloodstream. These days, transdermal patches are widely used as delivery systems for topical, transdermal, and cosmetic products.Transdermal patches work in different ways, as does the active medication ingredient's passage through the skin from the patch to the circulatory system.Etodolac transdermal patch acts as a type of controlled drug delivery system used to boost the efficiency,compliance and convenient to patients.Transdermal patches are novel methods to deliver a drug into skin at a controlled rate while maintaining the therapeutic concentration. In transdermal patches drug is administered via skin which is an integral part of transdermal drug delivery system. Skin serves numerous purposes. Along with offering protection from many types of stress, such as thermal, chemical, and UV radiation, it also acts as a barrier against infections and water loss. Through a variety of nerve endings, the skin communicates with our surroundings, controls body temperature, improves metabolic processes, and synthesizes vitamin D.The skin has two main layers: the epidermis, which covers our body and prevents water loss, and the dermis, which has many glands, blood vessels, and receptors. Skin plays an important role transdermal drug delivery system such as barrier and drug absorption.This etodolac transdermal patch acts as a very useful patch because the drug layer constitutes as a rate-controlling membrane for effective and controlled drug release. This review can acts as the base for future research on this topic